Effect of Re-steaming Treatment and Secondary Retrogradation on the Quality of Liuzhou Luosifen Rice Noodles - LIU Rong, WANG Dan, LI Yue, HUANG Yongchun (Shipin Kexue, 2025)
In order to explore the effects of the treatment with re-steaming and secondary retrogradation on the quality of Liuzhou Luosifen rice noodles, rice noodles were subjected to re-steaming and secondary retrogradation after initial retrogradation for 2 or 4 h and evaluated for cooking quality, texture characteristics, color, thermodynamic characteristics and microstructure. The results showed that the treatment with re-steaming and secondary retrogradation significantly changed the cooking quality of rice noodles, reducing the cooking loss rate by more than 21.6%, extending the rehydration time by more than 2 min, and increasing the rehydration rate by more than 10.0%. Texture analysis of rehydrated rice noodles showed that this treatment increased the hardness, elasticity and chewiness. The treatment slightly decreased the brightness value L* and increased the yellow/blue value b*. Furthermore, it increased the starting, peak and end temperature of rice noodles, and elevated the enthalpy value by more than 12.2%. Microstructure analysis indicated that the treatment promoted the short-range ordered rearrangement of starch chains, densifying the internal structure of rice noodles. In summary, the treatment with re-steaming and secondary retrogradation significantly impacted the quality and microstructure of Liuzhou Luosifen rice noodles. This study provides theoretical support for the quality improvement of Liuzhou Luosifen rice noodles.